Organic carbon and humic substances contents, carbon isotope composition and peroxidase activity in sediments from DSDP Sites 15-147 and 75-532 - Arie Nissenbaum; Andrei Serban (PANGAEA, 1987)
Sediment samples from the Cariaco Trench (DSDP Leg 15) and the Walvis Ridge (DSDP Leg 75) ranging in age from Holocene to Upper Miocene (approximately 8 million years BP) and in depth from 5 to 258 m were extracted with basic sodium pyrophosphate and the extract analyzed for enzymic activity. Since no dehydrogenase, alkaline phosphatase or esterase activity was found, it is estimated from these data that the maximum bacterial population does not exceed 1000 cells per gram dry sediment. Peroxidase activity was, however, found in most samples: this showed marked dependence on the humic substance concentration (expressed as percent of the organic carbon content) and increased with depth at a rate of 33 units per meter. To explain this observation, we favor an hypothesis based on the presence of active humic-enzyme association. The humic substances absorb and stabilize peroxidase which is liberated throughout the sediment column by lysis of cells. The association of the enzyme with the humic substances protects it from biodegradation and denaturation. This hypothesis agrees with laboratory experiments which show the enhanced stability of humic-enzyme complexes towards degradation by biological, chemical and thermal effects.
Supplement to: Nissenbaum, A; Serban, A (1987): Enzymatic (?) activity-associated with humic substances in deep sediments from the Cariaco Trench and Walvis Ridge. Geochimica et Cosmochimica Acta, 51(2), 373-378, https://doi.org/10.1016/0016-7037(87)90249-3